A mixed-methods approach to the psychological predictors of boredom in second language learning: mindfulness, grit, and self-regulation - Lyu, Jingjing (Frontiers in Psychology, 2025)
This mixed methods study explores the relationships among mindfulness, grit, self-regulation, and L2 boredom in Chinese undergraduate English majors. Using structural equation modeling (SEM) with a sample of 516 students from various universities, the quantitative phase found that mindfulness and grit were negatively related to L2 boredom, with self-regulation partially mediating these relationships. Mindfulness and self-regulation were the strongest predictors of reduced boredom, while grit had a smaller yet significant impact. Multi-group analysis showed these relationships were consistent across gender and years of English learning experience. The qualitative phase, involving focus group discussions with 40 participants, offered insights into students’ experiences. Boredom was described as a complex emotional, cognitive, and behavioral state leading to disengagement. Mindfulness helped students maintain focus, grit provided perseverance, and self-regulation offered strategies to manage boredom. Additionally, dynamic teaching methods and supportive environments were identified as crucial for reducing boredom and enhancing engagement. These findings enhance the understanding of psychological factors influencing L2 boredom and suggest practical strategies for educators to foster mindfulness, grit, and self-regulation, thereby improving student engagement and learning outcomes.